Coping and Regulating Emotions: A Pilot Study of a Modified Dialectical Behavior Therapy Group Delivered in a College Counseling Service - Meaney-Tavares, Rebecca; Hasking, Penelope (Routledge, 2013)
Objective: To analyze the efficacy of a pilot program, aimed at treating college students with borderline personality disorder (BPD) using short-term, modified group dialectical behaviour therapy at an Australian college counseling service (CCS). Participants: Seventeen enrolled college students aged between 18 and 28(76.5% female), with a diagnosis of BPD completed the program between November 2009 and November 2010. Methods: Participants attended 8 2-hour group therapy sessions, held at the CCS during semester. Participants were assessed for levels of depression, anxiety, BPD traits, and coping strategies, at commencement and completion of the program. Results: There was a reduction in symptoms of depression and BPD traits, and an increase in adaptive coping skills, including problem solving, and constructive self-talk. There was no reduction in anxiety. Conclusions: The findings indicate promise for short-term treatment of college students with BPD. Implications and limitations are discussed, with emphasis on replication with a control group.